A banana peel/silicon glue coated stir bar for extraction of aspirin, diclofenac, ibuprofen and mefenamic acid followed by high performance liquid chromatography-UV detection. Issue 36 (27th August 2020) - Jafari, Zahra; Hadjmohammadi, Mohammad Reza
Abstract : In the current study, a green, cost-effective, and bio-degradable additive was used for the preparation of a highly efficient sorbent based on silicon glue. Abstract : In the current study, a green, cost-effective, and bio-degradable additive was used for the preparation of a highly efficient sorbent based on silicon glue. Here, a banana peel was pretreated and mixed with silicon glue. It was proved that the prepared banana peel–silicon glue bar is a reliable sorbent for stir bar sorptive extraction of nonsteroidal anti-inflammatory drugs (NSAIDs) including aspirin, diclofenac, ibuprofen and mefenamic acid in human urine and plasma. Compared to the lab-made sorbents, the prepared sorbent showed high extraction performance, high stability, and satisfactory reproducibility and involved easy preparation. In order to optimize the effective factors, different parameters such as (stirring rate, pH, extraction time, desorption time and elution solvent volume) were optimized using response surface methodology (RSM) through applying Central-Composite Design (CCD). Under the optimum conditions, the linear dynamic ranges of the target analytes were investigated in the range of 0.2–200 μg L −1 with r 2 higher than 0.9929. Limits of detection (LODs) and limits of quantification (LOQs) of analytes were in the ranges of 0.04–0.5 and 0.15–1.65, respectively. The reproducibility of the method was also investigated by calculating the relative standard deviation. The RSD was measured to be lower than 4.9%. Bar-to-bar reproducibility at a 100 μg L −1 concentration level was also evaluated to be lower than 5.3% ( n = 3). Also, each prepared film can be used up to 64 times without any reduction in extraction performance. Finally, the method was successfully applied for the determination of selected drugs in different biological fluids including urine and plasma samples. The calculated relative recovery in real sample analysis was higher than 90%.